2020
DOI: 10.1002/erv.2813
|View full text |Cite
|
Sign up to set email alerts
|

Using bodily postures in the treatment of anorexia nervosa: Effects of power posing on interoception and affective states

Abstract: Power posing involves the adoption of an expansive bodily posture. This study examined whether power posing could benefit individuals with anorexia nervosa (AN) and women with normal weight in regards to interoceptive ability and affective states. Method: Participants included 50 inpatients and outpatients with AN as well as 51 normal-weight women. Interoceptive accuracy (IAcc), measured by the heartbeat tracking task and interoceptive sensibility (IS), measured by confidence ratings, were assessed at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…In detail, mediation analyses have shown that interoceptive sensitivity, as measured by a heartbeat-perception task, mediated the relationship between intuitive eating behavior (assessed by the intuitive eating scale) and BMI (Herbert et al, 2013). Conversely, impaired interoception has been reported for eating disorders, including bulimia nervosa, anorexia nervosa, and obesity (Pollatos et al, 2008;Klabunde et al, 2013;Herbert and Pollatos, 2014), while other studies found no differences between patients with bulimia nervosa or anorexia nervosa and healthy participants in a heartbeat detection task (Pollatos and Georgiou, 2016;Weineck et al, 2020). Similarly, whereas no difference emerged in heartbeat perception performance, Lutz and colleagues found larger HEP amplitudes in patients with anorexia nervosa compared to healthy controls (Lutz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In detail, mediation analyses have shown that interoceptive sensitivity, as measured by a heartbeat-perception task, mediated the relationship between intuitive eating behavior (assessed by the intuitive eating scale) and BMI (Herbert et al, 2013). Conversely, impaired interoception has been reported for eating disorders, including bulimia nervosa, anorexia nervosa, and obesity (Pollatos et al, 2008;Klabunde et al, 2013;Herbert and Pollatos, 2014), while other studies found no differences between patients with bulimia nervosa or anorexia nervosa and healthy participants in a heartbeat detection task (Pollatos and Georgiou, 2016;Weineck et al, 2020). Similarly, whereas no difference emerged in heartbeat perception performance, Lutz and colleagues found larger HEP amplitudes in patients with anorexia nervosa compared to healthy controls (Lutz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional interoception across various dimensions has been associated with AN ( Jenkinson et al, 2018 ; Martin et al, 2019 ). Regardless of the assessment method, whether subjective (e.g., questionnaires) or objective (e.g., heartbeat perception tasks), individuals with acute AN tend to exhibit lower self-reported interoceptive awareness (IA) ( Weineck et al, 2021 ; Phillipou et al, 2022 ) and reduced ability to accurately perceive bodily signals ( Pollatos et al, 2008 ) and discriminate between hunger and satiety sensations ( Fassino et al, 2004 ; Matsumoto et al, 2006 ). Impaired interoception, regardless of signal origin (gastric interoception, cardiac interoception or pain), has been observed in AN ( Martin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has been shown that assuming this body position of power can impact behaviour positively (e.g. performance at a job interview [Cuddy et al, 2015], general mood [Cuddy et al, 2018;Nair et al, 2015;Welker et al, 2013] and improve well-being for patients in the clinical context [Weineck et al, 2020]). Assuming that this position has also been found to induce hormonal and visceral changes (Carney et al, 2010(Carney et al, , 2015Laborde et al, 2019;Minvaleev et al, 2004;Nair et al, 2015).…”
Section: Introductionmentioning
confidence: 99%